New records of caridean shrimps (Decapoda: Caridea) from shallow water along the northern Yucatan peninsula coasts of México - Luis Daniel Santana-Moreno; Sammy De Grave; Nuno Simões (Nauplius)
The northern coast of the Mexican state of Yucatán has only been cursorily sampled in the past, with most of this effort concentrated on the largest coral reef in the Gulf of México, Arrecife Alacranes. The present study reports on recent collections (June 2008 - September 2013) of caridean shrimp in Yucatán, including Arrecife Alacranes and other reefs, as well as coastal lagoons and beaches. Additionally, a number of species are reported based on older, unidentified museum material. Six species represent new records for the Gulf of México [Janicea antiguensis (Chace, 1972), Gnathophyllum modestum Hay, 1917, Lysmata jundalini Rhyne, Calado and dos Santos, 2012, Periclimenes sandyi De Grave, 2009, Rapipontonia platalea (Holthuis, 1951a), Typton tortugae, McClendon, 1911], and 11 species are confirmed new records for México [Lysmata ankeri Rhyne and Lin, 2006, L. pederseni Rhyne and Lin, 2006, L. rafa Rhyne and Anker, 2007, Ascidonia miserabilis (Holthuis, 1951b), A. quasipusilla (Chace, 1972), Neopontonides chacei Heard, 1986, Periclimenaeus maxillulidens (Schmitt, 1936), P. pearsei (Schmitt, 1932), P. schmitti Holthuis, 1951b, Typton prionurus Holthuis, 1951b, Processa manningi De Grave and Felder, 2012], adding up to a total of 17 newly reported species for the East coast of México. Further, the colour pattern of several species is documented for the first time.